A Rare Case Report on Pyopericadium Progressing to Cardiac Tamponade - Yadav, Krishna; Laudari, Shankar (Journal of National Heart and Lung Society Nepal, 2022)
Pyopericardium is a rare condition with a high mortality in which infection propagates in the pericardial space leading to pus filled pericardial effusion and cardiac tamponade, which can cause cardiogenic shock and death. We present a case of previously healthy 79 years old male, who was diagnosed as Tubercular Pericardial effusion in IOM-TUTH, Maharajgung and on Antitubercular Therapy since 2 months. The patient didn’t respond well with the therapy and eventually presented to Chitwan Mutu Aspatal emergency with features of cardiac tamponade. It was confirmed on Two-Dimensional transthoracic Echocardiography and emergency pericardiocentesis drained frank pus around 1000ml. The patient was administered intravenous antibiotics along with continuation of Antitubercular Therapy and other supportive measures leading to gradual recovery of the patient and then discharged on antibiotics.